2018
DOI: 10.24974/amae.12.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Latinx Education Under Attack: The Implications of Immigration Policy for Education

Abstract: This conceptual article examines the intersection between immigration law enforcement and education. We explore the following questions: How have immigration and education policy intersected in the last decade, and particularly after the 2016 presidential election? To examine this question, we make use of the interdisciplinary nature of our own academic backgrounds as a political scientist and an education policy scholar to ground our article using sociologist Herbert Blumer’s sense of group position theory, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…During Donald Trump's first year in office, immigration continued to be a centerpiece of his agenda as he signed a far-reaching ban on immigration, which prompted protests at airports nationwide (ACLU-Washington, 2018). Moreover, he touted and implemented plans for a border wall between the United States and Mexico (Taylor, 2019), and inflamed anti-immigrant sentiment with racist language (López & Matos, 2018). More recently, his administration is responsible for the separation and inhumane detention of asylum-seeking families from Central America (Bala & Rizer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During Donald Trump's first year in office, immigration continued to be a centerpiece of his agenda as he signed a far-reaching ban on immigration, which prompted protests at airports nationwide (ACLU-Washington, 2018). Moreover, he touted and implemented plans for a border wall between the United States and Mexico (Taylor, 2019), and inflamed anti-immigrant sentiment with racist language (López & Matos, 2018). More recently, his administration is responsible for the separation and inhumane detention of asylum-seeking families from Central America (Bala & Rizer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In eight of these nine cases that involved an adult or a teenage child, their pursuit of employment resulted in their dropping out of school or taking time away from the pursuit of a higher degree. This outcome reflects just one of the many ways that exposure to immigration policing can affect the educational performance and accomplishment of young adults and children (see also Abrego 2006; Abrego and Gonzales 2010; Martinez 2014; Kerwin, Alulema, and Nicholson 2018; López and Matos 2018).…”
Section: Research Findings: the Implications Of Financial Losses For mentioning
confidence: 99%
“…Additionally, the issue of education and UIC is ongoing and new changes to policies affecting UIC may be underway, furthering the need for more research in this area. Although there is a growing amount of research about UIC, their access to education while apprehended remains underexamined in the literature (Ee & Gándara, 2020;Goździak, 2016;López et al, 2018;Rodriguez, 2021). Relatively little is known about the conditions of detention facilities, as U.S. Immigration and Customs Enforcement (ICE) shares a limited amount of publicly available information (Edyburn & Meek, 2021).…”
Section: A Critical Examination Of Policies and Practices Impacting T...mentioning
confidence: 99%
“…Scholars have also found that immigration enforcement under the Trump administration impacted academic outcomes and perceptions of school climate and culture of Latinx students (Kirksey & Sattin-Bajaj, 2021). President Trump's discourse and political actions demonstrated that racist nativism overtly affects the lives of immigrants in this country (López, 2020;López & Matos, 2018). Between Spring 2017 and July 2018, more than 4,000 families were separated at the border, leaving many children unaccompanied (Hoffman, 2019).…”
Section: Recent Political Developmentsmentioning
confidence: 99%